The Role of Digital Marketing in Increasing Brand Awareness of Klepon Legend Culinary Tourism in Gianyar - Herry Arianto Arianto; Dinar Sukma Pramesti (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This research aims to examine how digital marketing, especially video content on social media, influences brand awareness of Klepon Legend Gianyar and to identify strategies used by the business to increase sales through social media presence. Method: This study uses a qualitative descriptive approach. Data were collected through literature review from journals, books, and online sources, as well as analysis of public comments and responses on social media platforms related to Klepon Legend Gianyar. Result: The findings show that digital marketing through video-based social media content is effective in increasing brand awareness. In addition, endorsements and content sharing help spread information widely through electronic word-of-mouth (e-WoM), which supports higher customer interest and sales growth. Contribution: This research highlights the importance of digital marketing for promoting traditional culinary products in the modern era. It contributes new knowledge on how small culinary businesses can use social media strategies to strengthen brand awareness, preserve local food culture, and improve competitiveness in the digital market.